Ответы и объяснения

2013-02-13T11:49:50+00:00

1.

3*x+1/x-2 = 2*x-10/x+1

 x ∈ ∅; 

 x ∈ ∅;  x = -(sqrt(5)*sqrt(7)*%i-3)/2;x = (sqrt(5)*sqrt(7)*%i+3)/2;

 x=(217*корень(3)+440.448634916718)^(1/3)/3^(7/6)-26/(3^(5/6)*(217*корень(3)+440.448634916718)^(1/3))+1/3; 

 x=(217*sqrt(3)+440.448634916718)^(1/3)/3^(7/6)-26/(3^(5/6)*(217*sqrt(3)+440.448634916718)^(1/3))+1/3;  x = -((9*sqrt(5)*sqrt(479)+217*sqrt(3))^(2/3)*(sqrt(3)*%i+1)+26*3^(5/6)*%i-2*3^(1/6)*(9*sqrt(5)*sqrt(479)+217*sqrt(3))^(1/3)-26*3^(1/3))/(2*3^(7/6)*(9*sqrt(5)*sqrt(479)+217*sqrt(3))^(1/3));x = ((9*sqrt(5)*sqrt(479)+217*sqrt(3))^(2/3)*(sqrt(3)*%i-1)+26*3^(5/6)*%i+2*3^(1/6)*(9*sqrt(5)*sqrt(479)+217*sqrt(3))^(1/3)+26*3^(1/3))/(2*3^(7/6)*(9*sqrt(5)*sqrt(479)+217*sqrt(3))^(1/3));

 

2.

x+2/x-1+x/x+1 = 6/x^2-1

 x=(9*корень(307)+91*корень(3))^(1/3)/3^(7/6)-2/(3^(5/6)*(9*корень(307)+91*корень(3))^(1/3))-2/3; 

 x=(9*sqrt(307)+91*sqrt(3))^(1/3)/3^(7/6)-2/(3^(5/6)*(9*sqrt(307)+91*sqrt(3))^(1/3))-2/3;  x = -((9*sqrt(307)+91*sqrt(3))^(2/3)*(sqrt(3)*%i+1)+2*3^(5/6)*%i+4*3^(1/6)*(9*sqrt(307)+91*sqrt(3))^(1/3)-2*3^(1/3))/(2*3^(7/6)*(9*sqrt(307)+91*sqrt(3))^(1/3));x = ((9*sqrt(307)+91*sqrt(3))^(2/3)*(sqrt(3)*%i-1)+2*3^(5/6)*%i-4*3^(1/6)*(9*sqrt(307)+91*sqrt(3))^(1/3)+2*3^(1/3))/(2*3^(7/6)*(9*sqrt(307)+91*sqrt(3))^(1/3));